Injustice to Workers in the Shipbreaking Industry in South Asia: A Quest for a Civil Liability Framework in International Law - Ali, Mohammad (Curtin University, 2021)
This thesis raises the issues of global injustice to workers in the South Asian shipbreaking industry and stimulates a debate for introducing a civil liability framework in order to remedy the injustice. The thesis articulates the salient features of the civil liability framework- essential for ensuring the responsibility of all stakeholders in the maritime industry who profit from the business. It recommends an innovative business model for making the business both profitable and humane.